Effects of root extract of ashwagandha (withania somnifera) on perception of recovery and muscle strength in female athletes - Coope, O. C.; Salguero, A. R.; Spurr, T.; Calvente, A. P.; Farre, A. D.; Fisas, E. J.; Lloyd, B.; Gooderick, J.; Sangrà, M. A.; Roman-Viñas, B. (European Journal of Sport Science, 2025)
Ashwagandha is a supplement with the potential to improve exercise performance. However, research on its impact on female athletes remains limited. This study investigates the effects of ashwagandha on exercise recovery and muscle strength in professional female athletes, addressing a gap in understanding its role in this underrepresented population. Female footballers were randomly assigned to a 600 mg/day ashwagandha root extract group (ASH, n = 15; age: 26.0 ± 4.9 years, height: 1.66 ± 0.1 m, body mass: 61.5 ± 7.5 kg, and career: 15.2 ± 7.4 years) or a placebo group (PLA, n = 15; age: 23.5 ± 5.5 years, height: 1.66 ± 0.1 m, body mass: 61.5 ± 6.0 kg, and career: 13.1 ± 4.9 years). Recovery was assessed with total quality recovery (TQR), Hooper Index (HI) and rate of perceived exertion (RPE). Strength was assessed by hand grip, medicine ball throw (MBT), countermovement jump (CMJ) and peak power. Dietary intake was recorded prior to baseline measurements. Repeated measures ANOVA, Bonferroni test, independent t-tests and ANCOVA were used in the analysis. A significant group × time interaction effect was found for TQR (p = 0.026), with the post-hoc analysis revealing a significant difference between ASH and PLA at 28 days (p = 0.039). Perceived sleep quality from HI improved significantly in ASH compared to PLA (p = 0.038), with a significant change at 14 days. The ANCOVA analysis highlighted the significant influence of carbohydrate intake on hand grip strength (p = 0.005), MBT (p < 0.001) and body mass (p < 0.001). A dosage of 600 mg of ashwagandha root extract for 28 days may improve TQR and enhance perceived sleep quality in female footballers. Future research should investigate the optimal dosage and test across a broader range of athletic populations.